Research on technical scheme of SDN intelligent management and control orchestration system - Yanxia TAN; Guangquan WANG; Zelin WANG; Yanlei ZHENG; He ZHANG; Chenfang ZHANG; Sai HAN; Shikui SHEN (Dianxin kexue)
As users put forward more stringent quality of service requirements for the network, operators focus on the intelligent transformation and construction of various networks.Firstly, the current situation of software defined network (SDN) transformation and construction of various professional networks in the industry were briefly introduced, and then the problems existing in the transformation process were analyzed.Then, the scheme of SDN intelligent management and control orchestration system were proposed to meet users’ requirements for end-to-end service provisioning of cross professional services, and realize intelligent analysis of resource data at the network level to improve operation and maintenance efficiency.Finally, the service provisioning process of private line service and real-time alarming process and practice under the proposed architecture were introduced.